Ensuring Cultural and Cognitive Integrity in Instrument Translation: Quality of Life Index for Japanese Cancer Patients - Michiyo Mizuno; Keiko Sugimoto; Thomas Mayers; Carol Estwing Ferrans (Elsevier, 2019)
Objective: The objective of this paper is to provide a practical illustration of methods useful for translating and testing questionnaire instruments for nursing and healthcare to ensure reliability, validity, and appropriateness for the target culture. Methods: We present the process used to create the Japanese version of a well-established quality of life (QOL) instrument, originally developed in American English. The Ferrans and Powers Quality of Life Index (QLI)-Cancer Version III was translated into Japanese by a team of bilingual translators and tested using an iterative process involving cognitive interviewing with monolingual Japanese cancer patients. Results: Discussions among the translation team made it possible to find and resolve linguistic, cultural, and practical issues regarding the translation. Problems stemming from question interpretation and information retrieval were resolved through the cognitive interviewing process. One problem related to response editing could not be remedied with altered phrasing, namely a question referring to the respondents' sex lives. This item was retained in the Japanese version of the QLI as an indispensable component of QOL, particularly in a healthcare context. Conclusions: The final Japanese version captured the intended meaning of the original, and also was culturally appropriate and clearly understood by Japanese cancer patients.